Main Street public library : community places and reading spaces in the rural heartland, 1876-1956 - Wiegand, Wayne A., 1946- (Iowa and the Midwest experience., 2011)
The United States has more public libraries than it has McDonald's restaurants. By any measure, the American public library is a heavily used and ubiquitous institution. Popular thinking identifies the public library as a neutral agency that protects democratic ideals by guarding against censorship as it makes information available to people from all walks of life. Among librarians this idea is known as the "library faith." But is the American public library as democratic as it appears to be? In Main Street Public Library, eminent library historian Wayne Wiegand studies four.